DAMPAK AGROWISATA PADI SAWAH PALOH NAGA TERHADAP ASPEK SOSIAL-EKONOMI MASYARAKAT DESA DENAI LAMA KABUPATEN DELI SERDANG - andrew simanjuntak; Posman Marpaung; Robert Sinaga (Universitas Quality, 2021)
Denai Lama Village had unique potential to be developed into a large agro-tourism area in Deli Serdang Regency. The purpose of the study was to find out what people's views of lowland rice agrotourism in Paloh Naga are on the socio-economic status of the people of Denai Lama village and what are the opinions of managers of lowland rice agrotourism in Paloh Naga on the socio-economic impact in the village of Denai Lama. Respondents on this study were Denai Lama village officials, managers of lowland rice agrotourism in Paloh Naga, farmers, workers in agro-tourism, and traders in the traditional market of Paloh Naga. The results of this study indicated that the existence of lowland rice agro-tourism in Paloh Naga as an agro-tourism area had brought changes to the people of Denai Lama village. The positive impacts included the expansion of employment opportunities, increased income, pricing, village income, noise, increased intensity of mutual cooperation and agro-tourism waste. The negative impact was the occurrence of social jealousy in society.